Role of Malaysian trophy designers and manufacturers in promoting the use of symbols for custom-made trophies / Sharinah Md Nor - Md Nor, Sharinah (2005)
The principal objective of this study is to assist Malaysian trophy designers and manufacturers to improve their using symbols in trophy development processes through design recommendations from a custom-made trophy design perspective. This research study aims to help students of the Fine Metal Programme or individuals in any handicraft industry who want to be involved in custom-made trophy making to know the process of design and its execution. Chapter one discusses the background of trophy design and its manufacturing activities in Malaysia. Chapter two discusses the literature review to identify a rationale for the need because it provides the researcher with an overall framework of how the topic fits in the 'big picture' or what was known about the previous research. In chapter three, the research design has incorporated four inter-related phases. Phase One: Literature search and review, Phase Two: Questionnaire Survey and Interview, Phase Three: Case Studies and Phase Four: Observations. Chapter four shows the process of data collection including the problem arises during research for data collection. The research findings will benefit those who are involved in this industry. For trophy manufacturers, the research materials can be used as key factors in the formulation of company strategies. The research has identified the role of trophy designer and manufacturer and the part they play in the creating of using symbols in custom-made trophy designs in the face of Made in Malaysia trophy, globalization, and the implementation of Asian Free Trade Agreement (AFTA). The image of the trophy designers and manufacturers will improve in stature paving the way for more opportunities and recognition. This will lead to further improvement in custom-made trophies as part of the Malaysian craft industry for the local and international markets.